Denitrification using immersed membrane bioreactors - McAdam, Ewan J. (Cranfield University, 2008)
Nitrate is practically ubiquitous in waters abstracted for municipal potable water production in Europe due to decades of intensive agricultural practice. Ion exchange is principally selected to target abstracted waters with elevated nitrate concentrations. However, the cost associated with disposal of the waste stream has re-ignited interest in destructive rather concentrative technologies. This thesis explores the potential of membrane bioreactor (MBR) technology for the removal of nitrate from potable water. Two configurations are considered: an MBR to replace ion-exchange completely; and an MBR to treat the ion-exchange waste stream in-situ for re-use. For the replacement MBR, permeate quality can be affected by nitrite accumulation, micro-organism and carbon breakthrough. However, at steady-state and provided substrate addition was controlled, permeate quality was consistently high. Selection of an appropriate substrate was observed to improve permeability by a factor of three. Permeability was sustained within the MBR by adopting a dead-end filtration strategy having identified a relationship between filtered volume, flux and suspended solids concentration. Provided the filtered volume within a single filtration cycle did not exceed a set volume, the accumulated deposit was reversible. For the ion-exchange waste stream MBR, organic carbon breakthrough was considerable. However, the impact upon resin capacity was apparently limited when permeate was re-used for resin regeneration. Salt shocking did not induce permeability decline although some denitrification capacity was lost. Cost evaluation demonstrated that operating ion- exchange in parallel with MBR regenerant treatment was more cost effective than ion exchange with direct disposal.